2013
DOI: 10.1007/s00167-013-2784-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of platelet rich plasma (PRP) as an adjunct to microfracture surgery in osteochondral lesions of the talus

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(109 citation statements)
references
References 32 publications
2
104
0
1
Order By: Relevance
“…Several trials have reported superior functional outcome and improved histologic scores when comparing PRPenhanced microfracture versus microfracture alone. 10,11 Data regarding outcomes of BioCartilage use in human subjects are limited to expert opinion, but controlled human trials examining outcome differences between standard microfracture and BioCartilage techniques are currently under way. To date, an overall beneficial effect has been observed in more than 1,000 patients implanted with BioCartilage, with no adverse events related to this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Several trials have reported superior functional outcome and improved histologic scores when comparing PRPenhanced microfracture versus microfracture alone. 10,11 Data regarding outcomes of BioCartilage use in human subjects are limited to expert opinion, but controlled human trials examining outcome differences between standard microfracture and BioCartilage techniques are currently under way. To date, an overall beneficial effect has been observed in more than 1,000 patients implanted with BioCartilage, with no adverse events related to this therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of PRP preparations that mimic a native ECM milieu to recruit host progenitor/stem cells to enhance endogenous regenerative processes has also been proposed for further investigation [55]. In one study, when used as an adjuvant agent in arthroscopic microfracture surgery for the management of osteochondral lesions of the talus, PRP resulted in an improved functional status score in the medium term [606]. Additionally, when used in lumbar spine surgery for patients with posterolateral arthrodesis, a cancellous bone substitute soaked in PRP resulted in an enhanced fusion rate during the first 6 months after surgery and increased bone density, thus joining osteoinductive and osteoconductive effects [607].…”
Section: Formulations Enriched With Endogenous Growth Factorsmentioning
confidence: 99%
“…In a welldesigned randomized prospective study performed by Guney et al, 23 patients who received microfracture surgery were divided into 2 groups. Sixteen patients received treatment with microfracture surgery alone, whereas the remaining patients (PRP group, n = 19) were also given 1 dose of PRP the day after surgery.…”
Section: Discussionmentioning
confidence: 99%